2018
DOI: 10.3168/jds.2018-14669
|View full text |Cite
|
Sign up to set email alerts
|

Production of 15-F-isoprostane as an assessment of oxidative stress in dairy cows at different stages of lactation

Abstract: Oxidative stress contributes to dysfunctional immune responses and predisposes dairy cattle to several metabolic and inflammatory-based diseases. Although the negative effects of oxidative stress on transition cattle are well established, biomarkers that accurately measure oxidative damage to cellular macromolecules are not well defined in veterinary medicine. Measuring 15-F-isoprostane, a lipid peroxidation product, is the gold standard biomarker for quantifying oxidative stress in human medicine. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
2
26
0
2
Order By: Relevance
“…An antioxidant-reducing agent of 50% methanol, 25% ethanol, and 25% water with 0.9 mM butylhydroxytoluene, 0.54 mM EDTA, 3.2 mM triphenylphosphine, and 5.6 mM indomethacin, as described in Kuhn et al (2018), was added at 20 µL to 125 µL of thawed colostrum. Samples underwent lipid hydrolysis via the addition of 178 µL of KOH and incubating for 45 min at 45°C.…”
Section: Colostrum Pufa Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An antioxidant-reducing agent of 50% methanol, 25% ethanol, and 25% water with 0.9 mM butylhydroxytoluene, 0.54 mM EDTA, 3.2 mM triphenylphosphine, and 5.6 mM indomethacin, as described in Kuhn et al (2018), was added at 20 µL to 125 µL of thawed colostrum. Samples underwent lipid hydrolysis via the addition of 178 µL of KOH and incubating for 45 min at 45°C.…”
Section: Colostrum Pufa Analysismentioning
confidence: 99%
“…Then, 6 M HCl was added to the removed supernatant in increments of 10 µL until the supernatant pH was decreased to 4 or less. An internal standard mixture of 15 µL was added before undergoing solid-phase extraction with Oasis HLB 12-cm 3 LP extraction columns (Waters, Milford, MA) via a Biotage (Charlotte, NC) ExtraHera, further described in Kuhn et al (2018). Samples were then dried in a Savant SpeedVac (Thermo Fisher Scientific, Waltham, MA) and reconstituted in 1.5:1 methanol: HPLC water.…”
Section: Colostrum Pufa Analysismentioning
confidence: 99%
“…Les quelques études réalisées chez les rongeurs tendent à montrer que le lait et ses protéines peuvent jouer un rôle protecteur contre une augmentation du stress oxydant [28,34]. La capacité antioxydante du lait (vache, buffle) est, en grande partie, due aux vitamines A, E, aux caroténoïdes, au zinc, au sélénium et au système de défense anti-oxydante enzymatique (superoxyde dismutase, catalase, glutathion peroxidase).…”
Section: Effets Cardio-protecteurs Du Lait De Vacheunclassified
“…But, when the production of free radicals exceeds the antioxidants defense capacity, oxidative stress occurs (Batistel et al 2018). It has been reported that oxidative stress impairs cells' structures (especially immune cells) by damaging their macro components such as DNA, lipid and protein (Kuhn et al 2018). In addition, it is known that excessive oxidative stress can cause pathologic disorders of tissue and organ.…”
Section: Introductionmentioning
confidence: 99%